SOCIAL PREVENTION OF TUBERCULOSIS IN THE ARMED FORCES OF THE RUSSIAN FEDERATION - R. D. Muchaidze; V. V. Dantsev; Yu. N. Shitov; G. S. Balasanyants (Туберкулез и болезни лёгких)
The paper covers the content and significance of social preventive measures to control tuberculosis in the Armed Forces of the Russian Federation. Due to their recent reforms, the Armed Forces have taken new twists and military service has itself undergone drastic changes. A reduced call-up military service period, mainly a regional principle for recruitment, improved living, service, and resting conditions for the militaries, their better nutrition and food quality, improved military clothing, etc. have been an important contribution to social prophylaxis. In the past 6 years, only the above changes have caused tuberculosis morbidity to be reduced by more than 55% among the conscript servicemen. This is indicative of the importance of social measures. At the same time, all directions for tuberculosis control remain relevant among the militaries under the present conditions.